The Impact of the Use of Village Funds on Stunting Prevention Policies in Nagari Padang Lua, Agam Regency - Iva Puti Syavira; Rahmadani Yusran; Fitri Eriyanti; Zikri Alhadi (Science and Environmental Journal for Postgraduate, 2023)
This descriptive qualitative research examines the impact of village funds on stunting prevention policies in Nagari Padang Lua, Agam Regency. Data were collected from relevant agencies and parties in the village through interviews, observations, and documentation studies, then reduced to obtain accurate conclusions. The results show that the Nagari government has conducted stunting socialization, integrated healthcare center services for pregnant women and toddlers, and provision of the Supplementary Feeding Program (PMT) for toddlers. However, these programs have not been effective in preventing stunting due to the lack of involvement of pregnant women and parents of toddlers as the main targets, limited integrated healthcare center facilities and infrastructure, and low community participation and awareness.